Cerebellar hemorrhage in patients treated with edoxaban for portal vein thrombosis after hepatobiliary surgery: a report of two cases - Hiroya Iida; Toru Miyake; Masaji Tani; Takuya Tanaka; Kayo Kawakami; Yoshihiro Ikuno; Ryoichi Mandai; Tomoharu Shimizu (Surgical Case Reports)
Abstract Background The standard therapeutic agent administered for portal vein thrombosis (PVT) in patients with or without cirrhosis is warfarin or low-molecular weight heparin. However, therapy with edoxaban appears to be one of the most promising treatments for patients who require anticoagulation therapy. We encountered two cases of cerebellar hemorrhage in patients treated with edoxaban for PVT after hepatobiliary surgery during the past 2 years. Case presentation Case 1 A 67-year-old male underwent cholecystectomy and choledocholithotomy with choledochoduodenostomy to treat choledocholithiasis after cholangitis. Enhanced computed tomography (CT) on the 1st postoperative day (POD) revealed thrombosis in the left and anterior segment of the portal vein branches. We administered antithrombin III concentrate with heparin for 5 days; thereafter, we switched to 60 mg edoxaban. A sudden decrease in the patient’s level of consciousness was observed due to cerebellar hemorrhage on POD 27. Cerebellar hemorrhage was successfully treated with craniotomy hematoma evacuation and ventricular drainage; however, the patient died from aggravation of hepatic failure due to PVT and intra-abdominal infection. Case 2 A 67-year-old male received laparoscopic microwave coagulation therapy for two hepatic nodules suggestive of hepatocellular carcinoma in the left lobe of the liver due to alcoholic hepatitis. Enhanced CT on POD 5 revealed a thrombosis in the 4th segment branch of the portal vein, and the patient was treated with 60 mg edoxaban. Cerebellar hemorrhage with ventricular perforation occurred on POD 15. Cerebellar hemorrhage was successfully treated by craniotomy hematoma evacuation with ventricular drainage. Prolonged consciousness disorder persisted, and the patient was transferred to another medical facility for rehabilitation 49 days after brain surgery. Conclusions Although edoxaban is recently described to be one of the options for patients with PVT who require anticoagulation therapy instead of heparin or warfarin, it should be used with caution, given its propensity to induce severe hemorrhagic adverse events in cases such as those described above. The monitoring of hepatic dysfunction and decision for continuation of drug may be required during edoxaban use for PVT, especially after hepatobiliary surgery.